A COMPARATIVE STUDY OF THE IMPLEMENTATION OF ALTERNATIVE DISPUTES RESOLUTION (ADR) IN TAX AND CUSTOMS DISPUTES IN INDONESIA - ARDIANSYAH, ARDIANSYAH (Journal Evidence Of Law, 2022)
The implementation of Alternative Disputes Resolution (ADR) in customs disputes has not been carried out as the application of ADR in tax disputes in Indonesia has not been found. Is Indonesia deemed necessary to use ADR such as mediation as a settlement of tax and customs disputes. The research was conducted using a comparative approach to dispute resolution in the field of taxation in a number of countries. The results of the study conclude that it is possible for the parties involved in tax and customs disputes to resolve their disputes out of court by using mediation and negotiation facilities because the forms of settlement are very efficient and effective with practical, economical and uncomplicated procedures. The UK has been using mediation as an alternative to tax dispute resolution since 2011. Similar to Australia, the mediation process in the UK is facilitated to reach a mutual agreement through the help of a mediator. Strengthening the capacity of the Tax Court and the Tax Supervisory Committee as a tax ombudsman who participates in guaranteeing the rights of taxpayers. This strengthening is also accompanied by efforts to increase accountability and transparency. The role of the tax ombudsman in mediation has also been implemented in several countries, for example Prodecon in Mexico.